AN INDUSTRY-ORIENTED GAP ANALYSIS OF COMIC CURRICULUM IN CHINESE HIGHER EDUCATION - Wang, Xiaodong; Salim, Neesa Ameera Mohamed; Abd Jamil, Azhar; Ping, Liu (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study investigates the alignment between comic curricula in Chinese higher education institutions and the practical demands of the comics industry, employing a gap analysis approach. Semi-structured interviews were conducted with six senior industry experts from major cities in China, and the data were analysed using NVivo to identify primary industry expectations: creative skills at 60.59%, technical skills at 31.76%, and supporting skills at 7.65%. Curricula from two selected universities, totally 157 courses and 8,908 contact hours, were examined and categorised. The gap analysis revealed substantial undersupplies in creative courses (47.88% in contact hours) and technical skills (15.68%), contrasted with oversupplies in supporting (13.32%), practice (30.61%), and unrelated courses (19.63%). These discrepancies indicate a misalignment in resource allocation that affect graduate employability. The study suggests prioritizing creative and technical training, integrating industry-relevant practice, and reducing unrelated courses. For future study, expanding the scope to more universities or incorporating international comparisons could provide deeper insights into optimizing comic education.